2004
DOI: 10.1111/j.0105-2896.2004.00199.x
|View full text |Cite
|
Sign up to set email alerts
|

Cytokines in cancer immunity and immunotherapy

Abstract: The concept that the immune system recognizes and controls cancer was first postulated over a century ago, and cancer immunity has continued to be vigorously debated and experimentally tested. Mounting evidence in humans and mice supports the involvement of cytokines in tumor initiation, growth, and metastasis. The idea that the immune system detects stressed, transformed, and frankly malignant cells underpins much of the excitement currently surrounding new cytokine therapies in cancer treatment. In this revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
256
1
13

Year Published

2006
2006
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 360 publications
(274 citation statements)
references
References 183 publications
3
256
1
13
Order By: Relevance
“…Inflammatory mediators, such as COX-2 and cytokines, enhance tumorigenesis through the activation of multiple signaling pathways in tumor tissue (17,37). IL6 is a major proinflammatory cytokine that participates in inflammation-associated carcinogenesis (38,39) and has been reported to be positively linked with angiogenesis, EMT, and poor prognosis in esophageal cancer (20).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inflammatory mediators, such as COX-2 and cytokines, enhance tumorigenesis through the activation of multiple signaling pathways in tumor tissue (17,37). IL6 is a major proinflammatory cytokine that participates in inflammation-associated carcinogenesis (38,39) and has been reported to be positively linked with angiogenesis, EMT, and poor prognosis in esophageal cancer (20).…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence has indicated that inflammatory responses are important for cancer development (15,16). An increase in inflammatory mediators, such as COX-2 and proinflammatory cytokines has been shown to lead to tumor promotion, invasion, angiogenesis, and inflammation-associated intestinal tumorigenesis (17)(18)(19). In our previous study, IL6 has been demonstrated to link with aggressive tumor behavior and poor prognosis of esophageal SCC (20).…”
Section: Introductionmentioning
confidence: 94%
“…17 A range of tumor antigens has also been targeted using vaccines or adoptively transferred T cells. 18 However, with the exception of melanoma, tumors have proved to be poorly immunogenic thus far.…”
Section: Discussionmentioning
confidence: 99%
“…Among a continuous growing list of cytokines with antitumor potential (1), interleukin (IL)-15 appears as a candidate with especially promising features (2,3).…”
Section: Introductionmentioning
confidence: 99%